Spatial proportions of the future-oriented transport and infrastructural development of the Russian Federation - M. V. Ghukov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2014)
Spatial development challenges of Russia aggravate the problems of infrastructural sphere. The author gives a description of main priorities for the transport sector development in the medium term, evaluates territorial proportion of transports in the federal districts and identifies key problems of its individual modes’ development (railway, sea, inland waterway, highway, air). He draws conclusions related to the key priorities of spatial transport and infrastructure development and coordination of major measures and strategic planning documents.